Future public parks: integrating facilities for locative augmented reality games - Abdullah, Fadzidah; Noor, Mohd Faredzuan Mohd; Razak, Mohd Raziff Abd (Penerbit Akademia Baru, 2023)
Contemporary youth culture has caused public parks to be used as locations for them to play Locative Augmented Reality Games (LARG). Nevertheless, the existing public parks were not designed for LARG, which requires wide space for youth to have rigorous physical activities and movement. Therefore, there is a need to integrate facilities for players of LARG in the development of future public parks. This research aims to evaluate the characteristics and components of public parks often chosen by youngsters to play locative augmented reality games and to recommend additional facilities to be integrated into future public parks for all-inclusiveness. This research uses Vlog and On-site observation to evaluate components of public parks. It also employs an open-ended questionnaire survey for collecting primary data on needed additional facilities for future public parks. For reason of Movement Control Order (MCO) during the Covid19 pandemic, the research could evaluate only three (3) public parks that are located in Kuala Lumpur, Malaysia. The finding shows that public parks need design improvement to integrate spaces and facilities for Locative Augmented Reality games players (LARG). The research implies that the function of public parks evolves based on demands from visitors. This research indicates that public parks should be designed to cater for digital recreational activities, triggered by contemporary youth culture and relevant to the digital future.